2003
DOI: 10.1037/0022-3514.85.5.853
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment under social identity threat: The computer harassment paradigm.

Abstract: Two laboratory experiments investigated the hypothesis that threat to male identity would increase the likelihood of gender harassment. In both experiments, using the computer harassment paradigm, male university students (N=80 in Experiment 1, N=90 in Experiment 2) were exposed to different types of identity threat (legitimacy threat and threat to group value in Experiment 1 and distinctiveness threat and prototypicality threat in Experiment 2) or to no threat and were then given the opportunity to send porno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
384
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(407 citation statements)
references
References 55 publications
20
384
1
2
Order By: Relevance
“…To this end, recent research highlights the negative social reactions that non-conformists may suffer. Maas et al (2003) show that masculine males are more likely to engage in harassment, particularly when exposed to feminine information which may threaten their self-identity. Further, Rudman and Fairchild (2004) show how people who violate traditional stereotypes can suffer a social backlash from other members of their in-group.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, recent research highlights the negative social reactions that non-conformists may suffer. Maas et al (2003) show that masculine males are more likely to engage in harassment, particularly when exposed to feminine information which may threaten their self-identity. Further, Rudman and Fairchild (2004) show how people who violate traditional stereotypes can suffer a social backlash from other members of their in-group.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers initially believed that the reason for this was that more men in the company of fewer women would naturally lead to higher levels of harassment, recent research has shown that sexual harassment occurs more frequently in these organizations because male-dominated organizations generally involve careers that are traditionally held by men (e.g., construction workers, military). Maass, Cadinu, Guarnieri, and Grasselli (2003) argued that men sexually harass women because women threaten men's social identity by working in traditionally male roles. In their experiments, they manipulated social identity threat by pairing men with women who expressed either traditionally feminine (nonthreatening) gender roles or feminist (threatening) gender roles.…”
Section: Social Identity and Self-categorization Theories: Attacking mentioning
confidence: 99%
“…In previous studies, both masculinity and gender group identification predicted aggression after gender threat (Babl 1979;Maass et al 2003), but Experiment 1 showed no moderating effect of masculinity threat on aggressive cognitions. One possible explanation is that activation of the some concept in semantic memory can produce not only assimilation, but also inhibition effects (Newman and Uleman 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Gender schema are developed in every human being (Markus et al 1982), but some individuals use it very often in information processing and are susceptible to information related to gender (Markus et al 1982;Yan et al 2012). Previous studies showed that the masculinity threat exerts its effect primarily among masculine males (Babl 1979) and men who strongly identify with their gender group (Maass et al 2003;Schmitt and Branscombe 2001). Thus, it was hypothesized that the effect of a masculinity threat on accessibility of physically aggressive words would be moderated by the level of masculinity.…”
Section: Overview and Hypothesismentioning
confidence: 99%